Peloponneesolais-sota - Thucydides, 456? BCE-396 BCE; Hårdh, Emil (Salt Lake City, UT : Project Gutenberg, 2015)
"Peloponneesolais-sota" by Thucydides is a historical account written in the 5th century BC. It chronicles the devastating Peloponnesian War between Athens and Sparta, two mighty Greek powers locked in conflict. Written by an Athenian general who fought in the war, this unfinished work pioneered rigorous historical methodology through careful chronology and eyewitness testimony. Thucydides strips away divine intervention to reveal war's human causes, creating a stark, analytical record that strives for lasting truth rather than immediate entertainment. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_the_Peloponnesian_War
Release date is 2015-09-27
Produced by Juha Kiuru
Keywords: Greece -- History -- Peloponnesian War, 431-404 B.C.